Assessment of the mangrove community structure in Anhawan, Barangay Trapiche, Oton Iloilo. - Espinosa, Arleen Gamuzaran
Mangroves are a diverse group of predominantly tropical trees and shrubs growing in the marine intertidal zone where conditions are usually harsh, restrictive and dynamic. This study generally aimsto assess the community structure of mangroves in Barangay Trapiche, Oton Iloilo using ecological parameters, Specifically, this study also aims to: 1) determine the physical and chemical factors such as salinity, pH, and temperature of soil and water as well as characterization of substrates, mangroves have adapted to such factors giving them high tolerance to harsh environment; 2) to identify and classify the mangroves present in the area; and 3) describe the community structure in terms of Stand Basal Area, Stems per Hectare, Relative Density, Relative Frequency, Relative Dominance, Importance Values and Shannon Index of Diversity. The mangrove area was studied using the transect line plot method nine plots established., A total of nine true mangrove species were present in the area. These were Avicennia alba, Avicennia marina, Bruguiera cylindrica, Exoeccaria agallocha, Lumnitzera racemosa, Rhyzophora apiculata, Rhyzophora macronata, Rhizophora stylosa, and Sonneratia alba. Analysis of community structure of mangroves showed the following result. Average stand basal area is 24.35 msquared /ha, total stems per hectare is 717, Avicennia marina has the highest relative density of 21.058 percent and occurred frequently with 89 percent, makin it also the most important species with an importance value of 270. Bruguiera cylindrica dominated the area with relative dominance of 71.418 percent . The area was observed to be newly grown having a high seedling density, 74.20 percent repreented by Avicennia alba. The area has an index of H' = 0.86, and distribution of individual of various species was even. Physico - chemical factors seemingly influenced the mangrove community structure in this area.